The Effect of the Biomass Weight Ratio of Patchouli Leaves and Sawdust on the Chemical Properties of Patchouli Briquettes - Amal Muliono; La Oge; Erni Danggi; Rustan Ari; Hastian Hastian; Wa Ode Nur Siti Fatimah (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
The increasing depletion of fossil fuel reserves and rising global energy demand have accelerated the development of renewable energy sources, particularly biomass-based fuels. This study aimed to analyze the effect of biomass weight ratios of patchouli leaf waste and sawdust on the chemical properties and combustion rate of charcoal briquettes, and to determine the optimum composition for producing high-quality briquettes. The research was conducted in Wakumoro Village, Parigi District, Muna Regency, Southeast Sulawesi, from October to November 2025. A Completely Randomized Design (CRD) was applied with five treatment levels and three replications. The treatments consisted of different ratios of patchouli leaves and sawdust: P1 (100% patchouli leaves), P2 (75% + 25%), P3 (50% + 50%), P4 (25% + 75%), and P5 (100% sawdust). The observed parameters included moisture content, ash content, and combustion rate. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 95% confidence level. The results showed that biomass composition significantly affected moisture content, ash content, and combustion rate of briquettes. The best overall performance was obtained in P2, with moisture content of 1.57% and ash content of 7.48%, both meeting the Indonesian National Standard (SNI 01-6235-2000). The highest combustion rate was observed in P3 at 6.93 g/min. These findings indicate that the combination of patchouli leaf waste and sawdust has strong potential as an environmentally friendly alternative fuel and provides an effective solution for agricultural and wood waste utilization.